Multiple autonomy support attunement connections with perceived competence in learning and school grades among rural adolescents. - Simões, Francisco (2023)
In this study, we examine the associations of Multiple Autonomy Support Attunement (MASA) (corresponding to configurations of (in)consistent perceived multiple autonomy support regarding parents, teachers, and mentors) with perceived competence in learning and native language and math grades, among rural adolescents. A total of 448 ninth graders (M = 14.71; SD = .90; 58.03% girls) from The Azores Islands, a Portuguese mostly rural and isolated area participated in this study. Using Latent Class Analysis (LCA), a three-class solution for MASA presented the best fit and was more interpretable. Multivariate Analysis of Variance showed that unattuned MASA, due to low teacher support, was the most recurrent MASA configuration. While less recurrent, high MASA was associated with improvements in all educational outcomes. The effect of high MASA on improving educational outcomes among these youths was above and beyond, and more systematic, than factors that typically play a central role in rural educational trajectories, such as SES and gender. Our study shows the need to further articulate rural students’ social ecology features with the usual explanations for rural education failure.